2021
DOI: 10.1016/j.ajem.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of continuous use disposable N95 masks in clinical practice in the emergency department

Abstract: During the SARS-CoV-2 pandemic, many emergency departments (EDs) initiated continuous use of N95 disposable respirators (N95s) rather than discarding them after each use to conserve respirators. This study investigates the efficacy of wearing disposable N95s continuously during clinical work. Methods This is a prospective cohort study of ED staff required to wear N95s continuously throughout their shifts. Subjects were doctors, nurses, and technicians who were previously fitted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…[11][12][13] However, evidence of the safety of reuse practices in clinical settings is lacking, 14 as few prospective studies have been conducted to explicitly determine the incidence of fit failure during N95 reuse. [15][16][17] A pilot study conducted by some of us in 1 ED found that N95 reuse during increasing numbers of shifts was significantly associated with increased fit test failure. 15 These studies were limited, as single-center enrollment and cross-sectional designs did not permit definitive estimates of whether N95s could safely be reused.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[11][12][13] However, evidence of the safety of reuse practices in clinical settings is lacking, 14 as few prospective studies have been conducted to explicitly determine the incidence of fit failure during N95 reuse. [15][16][17] A pilot study conducted by some of us in 1 ED found that N95 reuse during increasing numbers of shifts was significantly associated with increased fit test failure. 15 These studies were limited, as single-center enrollment and cross-sectional designs did not permit definitive estimates of whether N95s could safely be reused.…”
Section: Introductionmentioning
confidence: 99%
“…15 These studies were limited, as single-center enrollment and cross-sectional designs did not permit definitive estimates of whether N95s could safely be reused. [15][16][17] We conducted a multicenter prospective cohort study of frontline HCWs across 6 EDs in the US to measure the incidence of qualitative fit test failure during N95 reuse, which included multiple donnings and doffings. We also sought to compare the incidence of fit test failure between HCWs across various N95 types.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations